A meta-analysis of the association between diabetic patients and AVF failure in dialysis. (15th October 2018) - Yan, Yan; Ye, Dan; Yang, Liu; Ye, Wen; Zhan, Dandan; Zhang, Li; Xiao, Jun; Zeng, Yan; Chen, Qinkai
Abstract: Purpose: The most preferable vascular access for patients with end-stage renal failure needing hemodialysis is native arteriovenous fistula (AVF) on account of its access longevity, patient morbidity, hospitalization costs, lower risks of infection and fewer incidence of thrombotic complications. Meanwhile, according to National Kidney Foundation (NKF)̸Dialysis Out-comes Quality Initiative (DOQI) guidelines, AVF is more used than before. However, a significant percentage of AVF fails to support dialysis therapy due to lack of adequate maturity. Among all factors, the presence of diabetes mellitus was shown to be one of the risk factors for the development of vascular access failure by some authors. Therefore, this review evaluates the current evidence concerning the correlation of diabetes and AVF failure. Methods: A search was conducted using MEDLINE, SCIENCE DIRECT, SPRINGER, WILEY-BLACKWELL, KARGER, EMbase, CNKI and WanFang Data from the establishment time of databases to January 2016. The analysis involved studies that contained subgroups of diabetic patients and compared their outcomes with those of non-diabetic adults. In total, 23 articles were retrieved and included in the review. Results: The meta-analysis revealed a statistically significantly higher rate of AVF failure in diabetic patients compared with non-diabetic patients (OR = 1.682; 95% CI, 1.429–1.981, Test of OR = 1: z  = 6.25, p  <.001). Conclusions: This review found an increased risk of AVF failure in diabetes patients. If confirmed by further prospective studies, preventive measure should be considered when planning AVF in diabetic patients.